2016
DOI: 10.1111/mec.13770
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity accurately predicts insect diversity in two tropical landscapes

Abstract: Plant diversity surely determines arthropod diversity, but only moderate correlations between arthropod and plant species richness had been observed until Basset et al. (2012, Science 338: 1481-1484) finally undertook an unprecedentedly comprehensive sampling of a tropical forest and demonstrated that plant species richness could indeed accurately predict arthropod species richness. We now require a high-throughput pipeline to operationalize this result so that we can (1) test competing explanations for tro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 61 publications
3
50
0
Order By: Relevance
“…Conversely, Pureora is comprised of several tree species, and individuals from Pureora have a smaller home range compared to Eglinton, suggesting a higher prey abundance and/or diversity (Toth, Cummings, Dennis, & Parsons, 2015). In other parts of the world, there is a positive relationship between and plant and insect diversity (Zhang et al., 2016). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, Pureora is comprised of several tree species, and individuals from Pureora have a smaller home range compared to Eglinton, suggesting a higher prey abundance and/or diversity (Toth, Cummings, Dennis, & Parsons, 2015). In other parts of the world, there is a positive relationship between and plant and insect diversity (Zhang et al., 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Eglinton, suggesting a higher prey abundance and/or diversity (Toth, Cummings, Dennis, & Parsons, 2015). In other parts of the world, there is a positive relationship between and plant and insect diversity (Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other BEF studies showed that the diversity of herbivorous arthropods (in particular dietary specialists) on trees is usually positively related to tree diversity, often via increased resource heterogeneity when larger and more diverse food resources increase herbivore diversity with effects transcending to predators (Scherber et al, 2010;Zhang et al, 2016). However, this association is less clear for leaf litter ants that are not dependent on the litter of particular tree species (Donoso et al, 2010) and have a broad range of dietary niches.…”
Section: Relationships Between Ant and Plot Versus Neighbourhood-scmentioning
confidence: 99%
“…For this, DNA metabarcoding approaches are the most frequently applied. Metabarcoding of bulk insect samples has, for example, been used to characterize the diversity of insects in montane landscapes in tropical southern China (Zhang et al, 2016), explore the insect diversity in a Saharo-Arabian region with otherwise sparse fauna information (Ashfaq et al, 2018), and monitor temporal changes in arthropod communities in different forest types (Brandon-Mong et al, 2018). Unique identifiers are added to sample amplicons before they are sequenced in parallel on a high-throughput sequencing platform.…”
Section: Introductionmentioning
confidence: 99%